The International Monetary Fund in a new international financial constellation: An interpretational commentary - David H. Pollock; Carlos Massad (CEPAL Review, 1978)
1. A ‘new’ IMF appears to be just now in process of emerging. If so, it will probably possess at least four central characteristics, namely: (a) it will be endowed with a significantly larger volume of loanable resources than before; (b) it will dispense those resources as part of a deliberate global policy primarily in order to find a way of recycling OPEC surpluses more efficiently than before; (c) it will undertake those new lending functions with a greater degree of ‘conditionality’ than before; and finally, (d) it will be granted a greater degree of ‘surveillance’ authority in so doing. These judgements stem from the following lines of reasoning.